Penggambaran Sikap Semangat Juang dalam Iklan Rexona Run #LanjutTerusStoryByRexona di Youtube Rexona Indonesia - Dewa Agustiar Saputra; Magvira Yuliani; Hendri Prasetya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores how the Rexona Run #LanjutTerusStoryByRexona advertisement on YouTube represents the spirit of perseverance. A qualitative approach is employed, using Roland Barthes’ semiotic method to analyze visual symbols and narrative elements. The research focuses on five inspirational scenes portraying individuals from diverse backgrounds: an elderly man who regains motivation after losing his wife, a housewife pursuing her dream of running amid family responsibilities, a boy striving to become a runner with his father's support, and a woman with physical limitations who overcomes doubt thanks to her supportive friends. The fifth scene unites these characters as they cross the finish line together, symbolizing the power of persistence and collective strength. The analysis reveals that the advertisement conveys its core message through sports movements, emotional expressions, and touching personal stories. The study also applies the Elaboration Likelihood Model (ELM), specifically the peripheral route, to explain how emotionally charged messages can influence viewers—especially when they are not in a rational or focused state. The ad goes beyond its marketing purpose, serving as a motivational medium that reinforces societal values around resilience and determination in the face of hardship. It emphasizes the importance of inner strength, external support, and the ability to find hope despite limitations. However, the research is limited by its scope, which focuses solely on content analysis and brief interviews without assessing the long-term impact of the advertisement’s message on audience attitudes or behavior.